From segregation to inclusive education: Examining the environmental adaptations on pupils with disabilities in regular schools within Yilo Krobo Municipality, Ghana - Asempa, Yvonne Emefa (Research Journal in Advanced Social Sciences, 2020)
Inclusive education is the adaptation and modification of the learning environment and instructions to promote the academic performance of all learners irrespective of race, class, gender, disability, sexual preference, religion, culture, learning styles, and language. Oppong (2003) explains inclusive education as the adaptation of the school curriculum to make it equally accessible to students with special needs. This means that the school curriculum should suit students with and without disabilities and the school environment should also be made equally accessible to students with special needs. The descriptive cross-sectional survey design was employed. A quantitative data collection method was used, thus eight Likert scale type questionnaire was designed for the selected primary school teachers in the Yilo Krobo Municipality, Ghana. This study brings to light the challenges faced by pupils with disabilities and further recommends possible measures that could be put in place to improve teaching and learning in regular schools.